AWARENESS OF GHARAR IN SALE AND PURCHASE CONTRACTS AMONG KUALA NERUS SOCIETY - Dr. Najdah Abd Aziz; Rafhanah Zakirah Rosley; Rubiah Abu Bakar (Journal of Islamic, Social, Economics and Development, 2022)
This study was conducted to identify the awareness of gharar in sale and purchase contracts in the society of Kuala Nerus, Terengganu. Any uncertainties, doubts and shortcomings in the sale and purchase contracts are considered gharar. Using the questionnaire as a research instrument, 120 sets were distributed through online forms among randomly selected Kuala Nerus society. The methodology of this study uses quantititave methods. Descriptive analysis is used to analyse data in percentage, frequency, mean, mode and median. The result of the investigation found that the mean value shown in each variable is high level, the value of mean part B is 4.233 and part C is 4.3833 (high). At the end of this study, the researcher suggested to conduct a more in-depth questionnaire on the understanding of gharar in the sale and purchase contracts. Researchers also suggest that other researchers develop their research aspects more widely, not only at the district level but also at the comparative level by state.